2010
DOI: 10.1001/archpediatrics.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Culturally Tailored Dance and Reducing Screen Time to Prevent Weight Gain in Low-Income African American Girls

Abstract: Objective-To test a 2-year community-and family-based obesity prevention intervention for low-income African-American girls.Design-Randomized controlled trial with follow-up measures scheduled at 6, 12, 18 and 24 months.Setting-Low-income areas of Oakland, CA.Participants-261 8-10 year old African-American girls and their parents/caregivers. Interventions-Families were randomized to two-year, culturally-tailored interventions: (1) after school Hip-Hop, African and Step dance classes and a home/family-based int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
193
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(202 citation statements)
references
References 57 publications
6
193
1
2
Order By: Relevance
“…24 One study reported on a physical activity intervention 23 ; all others reported on combination interventions including both diet and physical activity. Five of the studies were RCTs, 23,[25][26][27][28] and 4 of the studies were quasi-experimental. 24,[29][30][31] Six of the studies were conducted in the United States, 24,25,27-30 1 in Australia, 31 1 in Switzerland, 23 and 1 in the Netherlands.…”
Section: Study Settings and Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 One study reported on a physical activity intervention 23 ; all others reported on combination interventions including both diet and physical activity. Five of the studies were RCTs, 23,[25][26][27][28] and 4 of the studies were quasi-experimental. 24,[29][30][31] Six of the studies were conducted in the United States, 24,25,27-30 1 in Australia, 31 1 in Switzerland, 23 and 1 in the Netherlands.…”
Section: Study Settings and Intervention Characteristicsmentioning
confidence: 99%
“…Robinson et al' s 27 Stanford Girls Health Enrichment Multi-Site Study examined the impact of a community-and familybased obesity prevention program for low-income African American girls. The study included 261 African American girls aged 8 to 10 years and their parents or guardian and a follow-up period of 24 months.…”
Section: Study Settings and Intervention Characteristicsmentioning
confidence: 99%
“…27 Similarly, the link between physical activity and obesity are well established during later childhood, 28-33 yet less research has assessed the obesity risk associated with physical activity or sedentary activity (eg, screen time) during infancy. [28][29][30][31][32][33] Ethnicity, race, and culture can play an important role in our identities and our health behaviors, including dietary and physical-activity behaviors that may potentiate obesity. Although these relationships are beginning to be understood among older children, [34][35][36][37] we know less about the role of race/ ethnicity at the time when many of these behaviors are forged, namely the introduction of an infant into a family.…”
mentioning
confidence: 99%
“…Baker et al 15 Binkinet al 16 Blüheret al 17 Costa et al 18 Gabriele et al 19 Garcia et al 20 Jaballaset al 21 Klakket al 22 lee et al 23 marques et al 24 Nataleet al 25 Pallanet al 26 Pérez et al 27 Robinson et al 28 Vargas et al 29 Vasquez et al 30 1 Nos estudos descritos por Blüher et al 17 , Gabriele et al 19 , Jaballas et al 21 , Lee et al 23 e Robinson et al 28 (Tabela 1), realizados nos Estados Unidos, possuem na sua maioria o desfecho de identificar a eficácia dos métodos de prevenção e redução do número de crianças obesas, com exceção do estudo escrito por Jaballaset al 21 , que tem como objetivo constatar a percepção dos pais sobre o peso e situação que encontram-se seus filhos em relação a obesidade. Por mais que estes estudos tenham sido realizados no mesmo país, estes possuem diferenças, como por exemplo, o estudo realizado por Blüher et al 17 , apresentando um período delimitado de um ano.…”
Section: Parâmetros Avaliadosunclassified
“…Por mais que estes estudos tenham sido realizados no mesmo país, estes possuem diferenças, como por exemplo, o estudo realizado por Blüher et al 17 , apresentando um período delimitado de um ano. Já no estudo proposto por Robinson et al 28 teve como objetivo implementar o método de educação nutricional no ambiente escolar, sem tempo exato de término da intervenção. Na América Central, Garcia et al 20 desenvolveram um estudo randomizado controlado, com objetivo de descrer os resultados de um programa de adoção de estilo de vida saudável, aplicado por três anos, sendo avaliada a redução do índice de massa corporal (IMC) e do consumo de alimentos em escolares de duas comunidades Mexicanas, sendo aplicada a intervenção em 816 escolares, comparando com um grupo controle de 408 escolares.…”
Section: Parâmetros Avaliadosunclassified